Pengaruh Kualitas Produk dan Citra Merek Terhadap Loyalitas Konsumen Pada Mobil PT. Kalla Toyota Cabang Mall Ratu Indah di Kota Makassar - idha, Sulfaidah; Romadhoni, Buyung; Indrayani, Syhartini (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine the effect of product quality and brand image on consumer loyalty at PT. Kalla Toyota Mall Ratu Indah Branch in Makassar City. This research employed a quantitative method with an associative approach. Data were collected through questionnaires distributed to 170 respondents who are consumers of Toyota cars. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results show that partially, product quality has a positive and significant effect on consumer loyalty, with a t-value of 3.960 and a significance value of 0.000 (< 0.05). Brand image also has a positive and significant effect on consumer loyalty, with a t-value of 4.735 and a significance value of 0.000 (< 0.05). Simultaneously, product quality and brand image have a significant effect on consumer loyalty, with an F-value of 38.745 and a significance value of 0.000 (< 0.05). The coefficient of determination (R Square) of 0.457 indicates that 45.7% of the variation in consumer loyalty can be explained by product quality and brand image, while the remaining 54.3% is influenced by other factors not included in the research model. The findings indicate that brand image has a more dominant influence than product quality in increasing consumer loyalty. Therefore, the company should maintain and improve product quality and strengthen its brand image to enhance consumer loyalty at PT. Kalla Toyota Mall Ratu Indah Branch in Makassar City.